Those who can, teach: the academic quality of preservice students in teacher education programmes in Taiwan. Issue 1 (1st January 2016) - Wang, Hsiou-Huai; Huang, Chin-Chun
Abstract : Difficulty in recruiting high-calibre individuals into teaching is a perennial issue in the field of teacher education. In some countries, students in teacher programmes are in general found to be lower in academic standing than their counterparts in other fields, which might lead to belief in the old saying that "those who cannot, teach." In contrast to such discouraging phenomenon, based on analysis of a nationally representative data set, preservice students in Taiwan are found to be academically more outstanding than their nonteaching peers. Underlying policy and sociocultural contexts of such a positive phenomenon of "those who can, teach" are explained and implications for educators are discussed.